Pengaruh Cyber Public Relations Terhadap Citra Teguk (Survey Pada Pengunjung Gerai Teguk di Tangerang Selatan) - Rahmawati, Dewi Ika; Utari, Syifa Astasia (Educationist: Journal of Educational and Cultural Studies, 2023)
TEGUK is known as a typical street-foot thai tea boba drink that was established in 2018, it can be said that TEGUK has similar competitors. But now TEGUK has succeeded in building innovation in the FnB field with all the diversity and is active in disseminating information through its digital platform in maintaining and building a positive image. TEGUK has had a community, collaborated with well-known brands, entered the Shopee award nomination to successfully expand abroad. The purpose of this study was to determine whether there is an Effect of Cyber Public Relations on Teguk's Image (Survey of Visitors to Teguk Outlets in South Tangerang). The theories used in this study are Cyber Public Theory with the dimensions of Transparency, Internet Porosity, The Internet as an Agent, Richness in Content and Reach and Image with the dimensions of Perception, Cognition, Motivation and Attitude. This study uses a quantitative approach, survey method using a questionnaire. The population in this study were 758 who were TEGUK consumers. The sampling technique used Convenience Sampling with a total of 84 samples. The data obtained through IBM SPSS software that the analysis indicates Cyber Public Relations has an impact on TEGUK's brand image, while the rest is due to factors outside the study. In the hypothesis test, resulting in tcount 19.345 ttable 1.661, then Ho is rejected and Ha is accepted which means there is a significant influence between Cyber Public Relations on TEGUK Brand Image.